2018
DOI: 10.1177/2158244018769957
|View full text |Cite
|
Sign up to set email alerts
|

Coping and Help-Seeking Strategies Used by Students on the Intensive Foundation Program at the University of Brunei Darussalam

Abstract: Human resource development is one of the major goals of Brunei's current development plan to be achieved under Wawasan 2035 policy. The University of Brunei Darussalam's foundation program aims to increase students' access to higher education among disadvantaged and underrepresented groups. The present field survey investigated how the coping strategies and helpseeking behaviors of 146 (103 females and 43 males) Brunei foundation students would assist. Participants from government secondary schools scored sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The results showed that difficulties related to the during the corona pandemic were high with a mean of 2.40 and with a standard deviation of 0.31. This result is consistent with the results of other studies [15]- [19]. These results suggested that the wide-nation lockdown and the partial closure imposed by the corona crisis has affected the academic achievement of field training students.…”
Section: Discussion Of the Results Of The First Questionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results showed that difficulties related to the during the corona pandemic were high with a mean of 2.40 and with a standard deviation of 0.31. This result is consistent with the results of other studies [15]- [19]. These results suggested that the wide-nation lockdown and the partial closure imposed by the corona crisis has affected the academic achievement of field training students.…”
Section: Discussion Of the Results Of The First Questionsupporting
confidence: 92%
“…Students face many difficulties in field training, and these difficulties were divided into three types, namely: difficulties related to the student (the trainee), the training center (program), and the supervisors (the trainers) [7], [15]. Many studies suggested that the difficulties related to the trainer/student, included: the poor achievement of the students in other courses, unavailability of students, students' poor participation in 2273 activities organized by the university, and their inability to master practical skills [15]- [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeking help is a method in which a person reaches out to other people to assist him/her in overcoming the difficulties that the person could not overcome him/herself. During the process of help https://dx.doi.org/10.15405/epsbs.2019.04.02.113 Corresponding Author: Masitah Shahrill Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 913 seeking, the person seeks for emotional support, information, opinions as well as suggestions to overcome the psychological issues distressing him/her (Mundia, Shahrill, Jaidin, Jawawi, & Mahadi, 2016;Mundia & Shahrill, 2018a, 2018b. According to Rickwood, Deane, Wilson, & Ciarrochi (2005) there are two sources of help seeking: informal; and formal.…”
Section: Seeking Professional Psychological Helpmentioning
confidence: 99%
“…Until now, doctoral student research is considered quite ideal, in terms of approach and theory methods, analytical models, research methods, and the quality of the results. This research was also supported by Lawrence Mundia and Masitah Shahrill, who raised the topic of "Coping and Help-Seeking Strategies Used by Students on the Intensive Foundation Program at the University of Brunei Darussalam" (Lawrence Mundia and Masitah Shahrill, 2018) . James Kwan, by topic "Academic burnout, resilience level, and campus connectedness among methodologies, research methods, analytical models, and quality, doctorate programme student research is preferred.…”
mentioning
confidence: 99%